(untitled) (Research, Society and Development, 2020)
The present study aimed to evaluate the quality of minimally processed hard jackfruit submitted to different edible coatings, based on white sweet potato starch, purple sweet potato, breadfruit and chitosan. Eight treatments were developed, T1: without covering; T2: Chitosan 1% + Glycerol 2%; T3: White sweet potato 1% + Glycerol 2%; T4: Purple sweet potato 1% + Glycerol 2%; T5: Chitosan 1% + White sweet potato 1% + Glycerol 2%; T6: Chitosan 1% + Purple sweet potato 1% + Glycerol 2%; T7: Breadfruit 1% + Glycerol 2%; T8: Chitosan 1% + Breadfruit 1% + Glycerol 2%, these being applied to the jackfruit berries that were then stored for 12 days at 3 ° C, packed in expanded polystyrene trays and covered with polyvinyl chloride film ( PVC). The berries without covering and those submitted to other treatments, presented high levels of Total Extractable Polyphenols on the 12th day of storage. The berries treated with Chitosan 1% + Glycerol 2% (T2) obtained the best maintenance of appearance, with characteristics of freshness, shiny surface and absence of stains. The use of edible coating based on 2% Chitosan + 1% Breadfruit Starch + 2% Glycerol (T8) provided better physical-chemical quality, with less loss of mass, better correlation between loss of mass and appearance, and better consistency of soluble solids, acidity, pH and SS / AT, maintaining them in a satisfactory manner for commercialization, without prejudice to the physical-chemical quality characteristics for a period of 10 days.